The tenth biennial welfare report of the Australian Institute of Health & Welfare - Australian Institute of Health and Welfare (Australian Institute of Health & Welfare, 2011)
Australia’s welfare 2011 contributes to this discussion by bringing together the high-quality national statistics that form much of the evidence base for contemporary policy development.By providing an overview of the welfare sector in all its diversity, this report also highlights a number of important themes that transcend any individual component. These include the recognition that population ageing influences demand for welfare services beyond the scope of aged care; that the way we engage in education and work affects our need for government services and our capacity to provide informal care; and that while most Australians enjoy a high standard of living, disparities between population groups continue to exist.
Keywords: Government, law and policy; Government, law and policy